2007
DOI: 10.1007/s10722-006-9192-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and relationships among safflower (Carthamus tinctorius L.) analyzed by inter-simple sequence repeats (ISSRs)

Abstract: Genetic diversity and relationships among 48 safflower accessions were evaluated using 22 inter-simple sequence repeats (ISSR) primers. A total of 429 bands were amplified, and 355 bands (about 82.7%) were polymorphic. Five to forty-one polymorphic bands could be amplified by each primer, with an average of 16.1 polymorphic bands per primer. The results showed that the polymorphism of the safflower germplasm was higher at the DNA level. All the 48 accessions could be distinguished by ISSR markers and were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 17 publications
(21 reference statements)
8
41
2
Order By: Relevance
“…Yang et al (2007) had characterized 48 safflower accessions using ISSR markers and had reported similar conclusion when they had observed that accessions originating from Europe were relatively grouped together. These authors had also showed that the 48 accessions could be divided into nine groups by using UPGMA method.…”
Section: Figmentioning
confidence: 61%
“…Yang et al (2007) had characterized 48 safflower accessions using ISSR markers and had reported similar conclusion when they had observed that accessions originating from Europe were relatively grouped together. These authors had also showed that the 48 accessions could be divided into nine groups by using UPGMA method.…”
Section: Figmentioning
confidence: 61%
“…Recently, there is a raising interest in characterizing and exploiting its vast genetic diversity that can be further linked to desirable traits such as drought tolerance via molecular markers. Molecular markers have been used principally for the assessment of germplasm variability of local varieties, landraces, natural populations, and accessions in order to screen genetic diversity geographically (Amini et al 2008;Johnson et al 2007;Khan et al 2009;Sehgal and Raina 2005;Yang et al 2007). Since there is still inadequate genetic information, most of the markers did not require prior sequence information.…”
Section: Inferring Safflower Genetic Resource Diversitymentioning
confidence: 99%
“…Since there is still inadequate genetic information, most of the markers did not require prior sequence information. Hence, application of different molecular markers such as RAPD (Amini et al 2008;Mahasi et al 2009;Sehgal and Raina 2005;Vilatersana et al 2005), ISSR (Ash et al 2003;Golkar et al 2011;Panahi et al 2013;Sabzalian et al 2009;Yang et al 2007), AFLP (Johnson et al 2007;Sehgal and Raina 2005;Sehgal et al 2009), and SRAP (Mokhtari et al 2013;Peng et al 2008;Talebi et al 2012) has been successfully used in identifying genetic variety but had little to contribute for the identification of characteristics linked to drought tolerance. This may be the 'default' disadvantage of these marker systems since they 'scan' the genome arbitrary.…”
Section: Inferring Safflower Genetic Resource Diversitymentioning
confidence: 99%
“…Most of the genetic diversity that local and traditional varieties posses is being lost currently, so evaluation on the genetic diversity of safflower accessions available in different geographical regions will help to provide valuable information on the conservation and ultization of safflower germplasm (Yang et al 2007). In Iran, research efforts have been undertaken to diversify the farming systems and the government is encouraging the cultivation of various oilseed crops, including safflower (Mohammadi and Pourdad 2009).…”
Section: Introductionmentioning
confidence: 99%